2004
DOI: 10.1074/jbc.m408010200
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-mediated Suppressor of Cytokine Signaling Up-regulation Inactivates Growth Hormone Function

Abstract: Coordinated action between cytokines and chemokines is required for effective endocrine and immune responses. Proteins of both families promote receptor oligomerization, activation of the Janus kinase (JAK)/ STAT pathway, and transcription of many genes, including the suppressor of cytokine signaling (SOCS) family. In this study, we show that chemokine-mediated SOCS1 and SOCS3 up-regulation modulates the signaling and function associated to a cytokine receptor, both in vitro and in vivo. The effect is mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
2
15
1
Order By: Relevance
“…For example, whereas SOCS3 is expressed at low amounts in adult tissues, its expression can be upregulated by growth hormone and a number of cytokines, thus implicating SOCS3 in the negative feedback of cytokine signaling (Alexander, 2002;Johnston and O'Shea, 2003). In this regard, growth hormone-induced SOCS3 expression leads to blockade of JAK and Gi protein association with CXCR4 and impaired chemotaxis (Garzon et al, 2004;Pello et al, 2006;Soriano et al, 2003). In addition, heat shock protein has been reported to regulate CXCR4 signaling in T cells via a similar mechanism (Zanin-Zhorov et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…For example, whereas SOCS3 is expressed at low amounts in adult tissues, its expression can be upregulated by growth hormone and a number of cytokines, thus implicating SOCS3 in the negative feedback of cytokine signaling (Alexander, 2002;Johnston and O'Shea, 2003). In this regard, growth hormone-induced SOCS3 expression leads to blockade of JAK and Gi protein association with CXCR4 and impaired chemotaxis (Garzon et al, 2004;Pello et al, 2006;Soriano et al, 2003). In addition, heat shock protein has been reported to regulate CXCR4 signaling in T cells via a similar mechanism (Zanin-Zhorov et al, 2005).…”
Section: Discussionmentioning
confidence: 94%
“…As SOCS1 expression can also be enhanced by growth hormone (Fasshauer et al, 2004;Garzon et al, 2004;Larsen and Ropke, 2002), our findings suggest a novel way of cross-talking between cytokine and RTK receptors.…”
Section: Journal Of Cell Science 119 (2)mentioning
confidence: 92%
“…23 Similar effects are induced by SOCS1, which binds JAK to abrogate later signaling events. 55 The higher levels of circulating Sca-1 ϩ c-Kit ϩ Lin Ϫ cells in bGHTg than in wt mice suggested that these effects were due to SOCS-mediated blockade of CXCR4 function. Administration of rhGH to wt mice reproduced the bGHTg mouse phenotype.…”
Section: Discussionmentioning
confidence: 99%